Study on The Distribution of Longtail Tuna (Thunnus Tonggol) Catch Based on Chlorophyll-A Using Aqua Modis Imagery in West Sumatera - Muhammad Farhan Al Iqromi; Afriani Harahap; Heltria, Septy; Farhan Ramdhani; Ester Restiana Endang Gelis; Hutwan Syarifuddin (Grouper, 2025)
The longtail tuna (Thunnus tonggol) is one of the highest-producing fishery commodities in the waters of West Sumatra. Its abundance is influenced by oceanographic conditions, particularly indicated by chlorophyll-a concentration as a marker of water productivity. This study aims to examine the distribution of chlorophyll-a in relation to the catch of longtail tuna (Thunnus tonggol) using Aqua MODIS imagery in the waters of West Sumatra. The method used in this research is observational, involving data collection on chlorophyll-a distribution and logbook records. Chlorophyll-a data was obtained from the Ocean Color website, and logbook data for 2018–2022 was sourced from the Bungus Oceanic Fisheries Port (PPS). The results show that chlorophyll-a distribution in the waters of West Sumatra fluctuated between 2018 and 2022, with an average range of 0.15 mg/m³ to 0.33 mg/m³. A simple linear regression analysis showed a significant F-value of 0.0045, which is smaller than α (0.05), indicating that the regression equation is valid. This suggests that the distribution of chlorophyll-a has a significant effect on the longtail tuna catch in the waters of West Sumatra. The average annual CPUE (Catch Per Unit Effort) of longtail tuna was 0.44 tons/trip, with an average catch over the 2018–2022 period of 18.38 tons and an average of 41 trips per year.